1964
DOI: 10.1021/ac60209a053
|View full text |Cite
|
Sign up to set email alerts
|

Application of Thin Layer Chromatography to the Analysis of Atmospheric Pollutants and Determination of Benzo(a)pyrene.

Abstract: The CoY-2 was generated in the electrode cavity by reduction of 1.0 X 1C-2F CoYwhich is a substitution-inert complex. The solution contained 0.50F NaBr to increase the reversibility of the CoY-2 oxidation (1). The experiment consisted of generating CoY-2 for a measured time, tf, turning off the current for time, td, and then reversing the direction of current flow and recording an anodic chronopotentiogram corresponding to the amount of CoY-2 which had not reacted with the excess Ni+2 ion. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1965
1965
1986
1986

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Consequently, it is important to develop effective, quantitative separation techniques for the analysis of PAH compounds in air particulate samples, including the isolation of the individual components of isomeric groups that differ greatly in toxicity. Reported separation schemes employing thin-layer chromatography (5)(6)(7), adsorption chromatography and charge-transfer complexation (8), paper chromatography (9), and mass fragmentometry (10) have met with only limited or little success in the separation of isomers.…”
mentioning
confidence: 99%
“…Consequently, it is important to develop effective, quantitative separation techniques for the analysis of PAH compounds in air particulate samples, including the isolation of the individual components of isomeric groups that differ greatly in toxicity. Reported separation schemes employing thin-layer chromatography (5)(6)(7), adsorption chromatography and charge-transfer complexation (8), paper chromatography (9), and mass fragmentometry (10) have met with only limited or little success in the separation of isomers.…”
mentioning
confidence: 99%
“…The fine structure present is attributed to singlet-triplet transitions [82], and the general absorption underlying it is the result of charge transfer between the benzene (donor) and the oxygen (acceptor) . has sometimes been recommended that the chromat opiates be read while they are still wet [84,85] we have found that the presence of solvent often accelerates the changes in the spots. Although it has been pointed out that some adsorption of a solute may occur during filtrations [87], there is apparently no general awareness of the possible magnitude of such losses with dilute solutions of certain solutes.…”
Section: Fhenylhydrazono-phenylazo Compoundsmentioning
confidence: 89%
“…Tanner and co-workers [183,185,186] have used the collimated structure diffusion battery for the size-fractionated sampling and analysis of sulphate aerosols in the New York atmosphere. Ambient samples were collected directly and after passing through the battery.…”
Section: Diffusion Batterymentioning
confidence: 99%
“…The apparatus is shown schematically in Fig. This design has the advantage over the apparatus of Tanner and co-workers [183,185,186] that very large particles are pre-separated by the cascade impactor and do not enter the diffusion battery where they may be intercepted, giving a misleading picture of size distributions. Air enters the system into an Andersen 4-stage Hi-Vol impactor initially, where particles are separated into fractions of aerodynamic diameter > 7 flm; 3.3-7 flm; 2-3.3 flm; 1.1-2 flm and < 1.1 flm.…”
Section: Diffusion Batterymentioning
confidence: 99%
See 1 more Smart Citation